Antibacterial action of graphene oxide towards bacteria and its toxicological effects on human epidermal keratinocytes / Thiruchelvi Pulingam - Thiruchelvi , Pulingam (2020)
The antibacterial nature of graphene oxide (GO) has stimulated wide interest in the medical field. Although the antibacterial activity of GO towards bacteria has been well studied, a deeper understanding of the mechanism of action of GO is still lacking. The objectives of the study were to characterize the physicochemical properties of GO, to determine the antibacterial and antibiofilm activity and the mechanistic action of GO against Gram-positive Staphylococcus aureus and Enterococcus faecalis and Gram-negative Escherichia coli and Pseudomonas aeruginosa, to determine the synergistic behaviour of GO with selected antibiotics against bacterial cells in suspension and biofilm and to determine the in vitro toxicological effects of GO against human epidermal keratinocytes (HaCaT). GO was characterized using Ultraviolet-visible (UV-VIS), Raman and Attenuated Total Reflectance-Fourier-transform infrared (ATR-FTIR) spectroscopy techniques, Field Emission Scanning Electron Microscopy (FESEM), Transmission Electron Microscopy (TEM) and X-Ray Diffraction analysis (XRD) techniques. Viability, time-kill and Lactose Dehydrogenase (LDH) release assays were carried out to determine the antibacterial activity of GO towards bacterial cells in suspension and biofilm while FESEM and TEM analysis were conducted for GO treated bacterial cells in suspension. Interactions at molecular level between GO and antibiotics were analyzed using ATR-FTIR and UV-Vis techniques. Increase in the activity of antibiotics through the addition of GO was investigated using selected antibiotics such as ampicillin, chloramphenicol and tetracycline. Additionally, toxicity of GO towards HaCaT cells were examined through 3-(4,5-Dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) viability, reactive oxygen species (ROS) detection and LDH release assays while surface morphology of GO treated HaCaT cells were analyzed using FESEM. Characterization techniques confirmed the presence and morphology of GO in sheet-like formation. Antibacterial activity of GO was concentration and time-dependent for the bacterial cells in suspension. Optimal GO concentration with more than 60% of bacterial cell death was at 10 μg/mL. In contrast, GO enhanced the viability of the biofilm cells when treated with higher concentrations and for longer exposure period. Loss of membrane integrity among bacteria in suspension was enhanced with increasing GO concentrations and this corresponded to the elevated release of LDH in the reaction medium. Bacterial cell morphology of GO treated bacterial culture showed apparent differences in the mechanism of action of GO towards Gram-positive and Gram-negative bacteria. ATR-FTIR characterizations of the GO treated bacterial cells showed changes in the fatty acids, amide I and amide II of proteins, peptides and amino acid regions compared to untreated bacterial cells. The ATR-FTIR and UV-Vis characterizations of GO and antibiotics showed adsorption of tested antibiotics onto GO through molecular interactions. The combinatorial antibacterial activity of GO and antibiotics towards bacteria in suspension was found to be increased when compared to GO or antibiotic alone but no changes were observed with the biofilm cells. Cytotoxicity of GO was found to be dose dependent towards HaCaT cell line and hence it is suggested to impose only low toxic effects against the epidermal keratinocytes. Therefore, this study reaffirms that GO has strong antibacterial potentials and could act as an adjuvant to enhance the antimicrobial activity of antibiotics.